RETRACTED: Do renewable energy consumption and financial development contribute to environmental quality in MINT nations? Implications for sustainable development - Adebayo, Tomiwa Sunday; Ağa, Mehmet; Agyekum, Ephraim Bonah; Kamel, Salah; El-Naggar, Mohamed F. (Frontiers in Environmental Science, 2022)
Maintaining a balance between the well-being of the economy and the environment has become a top priority for governments globally. In the contemporary age, world economies, particularly the emerging ones like MINT nations, highlight the need for green growth. The MINT nations are thriving economically but are having difficulty reducing their ecological footprint (EF). Therefore, this paper aimed to determine if factors such as population density, renewable energy, foreign direct investment, economic growth, and financial development impacted ecological footprint in the MINT countries between 1990 and 2018. The study applied ample advanced econometrics such as method of moments quantile regression (MMQR), augmented mean group (AMG) and Correlated Effects Mean Group (CCEMG). The overall results indicated that the variables are integrated at the first difference and are cointegrated. The AMG, CCEMG and MMQR results reveal that economic growth deteriorates ecological well-being by promoting the EF while foreign direct investment, population density and renewable energy enhance the environment by mitigating the EF in the MINT nations. In addition, financial development does not exert a significant effect on EF. The Dumitrescu Hurlin Panel Causality results show unidirectional causality from economic growth, financial development, population density, and renewable energy to EF. Based on these results, policy recommendations are suggested